FACTORS AFFECTING BACTERIOLOGICAL DAMAGE MUSCLE LICE - Azizov Dilmurod Homidzoda; Muzaffarov Omon Maratovich; Ziyodullayeva Zarnigor Ziyodullayevna; Qurbonova Saodat Muzaffarovna (Web of Journals Publishing, 2025)
The article theoretically analyzes the main internal (endogenous) and external (exogenous) factors that affect the process of muscle tissue regeneration against the background of bacterial infections. During the study, such mechanisms as the negative impact of pathogens Staphylococcus aureus, Clostridium perfringens on myofibrillary structure, such mechanisms as necrosis, inflammation, violation of angiogenesis and fibrosis formation are elaborately illuminated. The role of factors such as the state of the immune system, age, hormones, nutrition and oxygen supply in the recovery of muscle tissue is assessed. It also analyzes antibiotic therapy, biostimulants and modern methods of rehabilitation, and proposes conceptual directions for further scientific and experimental research. This theoretical study substantiates the need for a better understanding of the processes of muscle regeneration, improvement of clinical rehabilitation approaches as well as an in-depth study of this problem in the conditions of Uzbekistan.
Keywords: Bacterial infection, muscle tissue, regeneration, myofibrils, necrosis, angiogenesis, immune system, antibiotic therapy, fibrosis, rehabilitation, biostimulants, Uzbekistan healthcare.